2017
DOI: 10.1159/000471918
|View full text |Cite
|
Sign up to set email alerts
|

Eplerenone Prevents Atrial Fibrosis via the TGF-β Signaling Pathway

Abstract: Objectives: Eplerenone (EPL), an antagonist of the mineralocorticoid receptor, is beneficial for atrial fibrillation and atrial fibrosis. However, the underlying mechanism remains less well known. We aimed to investigate the effect of EPL on atrial fibrosis using a mouse with selective atrial fibrosis and to explore the underlying mechanisms. Methods: EPL-treated MHC-TGFcys33ser transgenic mice that have selective atrial fibrosis (Tx+EPL mice), as well as control mice, were used for in vivo studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
8
1
1
Order By: Relevance
“…Previous studies found that spironolactone reduced the content of the collagen fiber content in other tissues, such as in the myocardium [38,39]. Although, previous studies reported that eplerenone had similar anti-fibrotic effects on the myocardial tissue [40], in our study, eplerenone treatment did not significantly reduce adrenal capsule width. The mechanisms behind the spironolactone effect on the adrenal capsule are still unknown; however, although it is positive in the myocardium context, the consequences of a reduction of the connective tissue of the adrenal gland may compromise the gland structure.…”
Section: Discussioncontrasting
confidence: 76%
“…Previous studies found that spironolactone reduced the content of the collagen fiber content in other tissues, such as in the myocardium [38,39]. Although, previous studies reported that eplerenone had similar anti-fibrotic effects on the myocardial tissue [40], in our study, eplerenone treatment did not significantly reduce adrenal capsule width. The mechanisms behind the spironolactone effect on the adrenal capsule are still unknown; however, although it is positive in the myocardium context, the consequences of a reduction of the connective tissue of the adrenal gland may compromise the gland structure.…”
Section: Discussioncontrasting
confidence: 76%
“…The RAAS is progressively considered a critical player in cardiac fibrosis development. 53 Angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs) [54][55][56][57][58][59] and mineralocorticoid receptor antagonists [60][61][62][63] can reduce atrial fibrosis progression and AF susceptibility, as demonstrated by multiple experimental studies (Table 1). 64 Retrospective trials and meta-analyses of randomized studies demonstrated that administration of ACEIs or ARBs with ACEIs/ARBs of these diseases may have been confounded by indications.…”
Section: Renin-angiotensin-aldosterone System (Raas) Antagonistsmentioning
confidence: 99%
“…Furthermore, inhibition of TGF‐β1/Smad3 signaling pathway can prevent cardiac reconstruction and release diastolic cardiac dysfunction (Ramos‐Mondragon, Galindo, & Avila, ). Over‐expression of TGF‐β1 is related to atrial fibrosis much more than ventricular fibrosis (Du et al, ). According to our results, compared to the Wistar rats, the protein levels of Smad3 and p‐Smad3 increased significantly in atrium lysates from SHRs.…”
Section: Discussionmentioning
confidence: 99%